The fate of a southwest Pacific bloom: gauging the impact of submesoscale vs. mesoscale circulation on biological gradients in the subtropics - A. de Verneil; L. Rousselet; A. M. Doglioli; A. A. Petrenko; T. Moutin (Biogeosciences, 2017)
The temporal evolution of a surface chlorophyll a bloom sampled in the western tropical South Pacific during the 2015 Oligotrophy to UlTra-oligotrophy PACific Experiment (OUTPACE) cruise is examined. This region is usually characterized by largely oligotrophic conditions, i.e. low concentrations of inorganic nutrients at the surface and deep chlorophyll a maxima. Therefore, the presence of a surface bloom represents a significant perturbation from the mean ecological state. Combining in situ and remote sensing datasets, we characterize both the bloom's biogeochemical properties and the physical circulation responsible for structuring it. Biogeochemical observations of the bloom document the bloom itself, a subsequent decrease of surface chlorophyll a, significantly reduced surface phosphate concentrations relative to subtropical gyre water farther east, and a physical decoupling of chlorophyll a from a deep nitracline. All these characteristics are consistent with nitrogen fixation occurring within the bloom. The physical data suggest surface mesoscale circulation is the primary mechanism driving the bloom's advection, whereas balanced motions expected at submesoscales provide little contribution to observed flow. Together, the data provide a narrative where subtropical gyre water can produce significant chlorophyll a concentrations at the surface that is stirred, deformed, and transported great distances by the mesoscale circulation. In this case, for the time period considered, the transport is in an easterly direction, contrary to both the large-scale and mean mesoscale flow. As a result, future studies concerning surface production in the region need to take into account the role complex mesoscale structures play in redistributing subtropical gyre water.